2009
DOI: 10.1016/j.bbapap.2009.01.007
|View full text |Cite
|
Sign up to set email alerts
|

A novel vanadium reductase, Vanabin2, forms a possible cascade involved in electron transfer

Abstract: The unusual ascidian ability to accumulate high levels of vanadium ions at concentrations of up to 350 mM, a 10(7)-fold increase over that found in seawater, has been attracting interdisciplinary attention for a century. Accumulated V(V) is finally reduced to V(III) via V(IV) in ascidian vanadocytes. Reducing agents must therefore participate in the reduction. Previously, we identified a vanadium-binding protein, Vanabin2, in which all 18 cysteines form nine disulfide bonds. Here, we report that Vanabin2 is a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 26 publications
1
63
0
1
Order By: Relevance
“…The 15 N HSQC spectra provided information regarding the amino acids implicated in the V IV binding as their resonances are missing or altered when compared to the native spectrum ( Fig. 3) [47]. In fact, the obtained results show that V IV ions, which are exclusively localized on the same face of the molecule, are coordinated by amine-N donors from lysines, arginines and histidines, corroborating the EPR and ESEEM data previously collected [44] [45].…”
Section: Of 135supporting
confidence: 87%
See 1 more Smart Citation
“…The 15 N HSQC spectra provided information regarding the amino acids implicated in the V IV binding as their resonances are missing or altered when compared to the native spectrum ( Fig. 3) [47]. In fact, the obtained results show that V IV ions, which are exclusively localized on the same face of the molecule, are coordinated by amine-N donors from lysines, arginines and histidines, corroborating the EPR and ESEEM data previously collected [44] [45].…”
Section: Of 135supporting
confidence: 87%
“…and have also been recognized as V IV binding proteins [47]. Structural modeling of vanabins 1, 3, and 4, based on the NMR data of vanabin2, resulted in fairly good homologous structures.…”
Section: Of 135mentioning
confidence: 98%
“…The family of vanabins now includes at least five closely related small proteins (vanabin1 to vanabin 4 and vanabin P) of approximately 90 a.a. (Kawakami et al 2009). Novel vanadium binding proteins not homologous to vanabins have been recently isolated from blood cells of A. sydneiensis samea, including VBP129, AsGST-I, and AsGST-II having a striking homology to glutathione S-transferases (Yoshihara et al 2008).…”
Section: Discussionmentioning
confidence: 93%
“…These processes have been well characterized in ascidian vanadocytes where vanadium accumulated from seawater is bound to vanabins in the cytosol and reduced from V(V) to V(IV) in the presence of GSH, forming an electron transfer cascade from NADPH, via glutathione reductase and vanabin2, to the vanadium ions conjugated through thiolsulfide exchange reactions (Michibata et al 2002;Ueki et al 2003;Kawakami et al 2009). The V(IV) would be transported into vacuoles and further reduced to V(III) by unknown reductants.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, our group reported that Vanabin2 can act as a V V -reductase in a thiol-disulfide exchange reaction cascade that included GSH and NADPH [27]. To examine the possibility that such a reduction can occur in blood plasma, we performed ESR analysis to examine V V -reductase activity of VBP-129 as described previously.…”
Section: Reduction Of V V By Vbp-129mentioning
confidence: 99%